2022
DOI: 10.5114/biolsport.2022.103575
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of plyometric and isometric strength training on dynamic and isometric force-time characteristics

Abstract: The purpose of the study was to compare the change in dynamic and isometric force-time characteristics after plyometric (PLYO) or isometric strength training (ISO). Twenty-two endurance runners (age = 37 ± 6 years, stature = 1.71 ± 0.05 m, body mass = 62.7 ± 8.6 kg, weekly mileage = 47.3 ± 10.8 km) performed a countermovement jump (CMJ) and isometric mid-thigh pull (IMTP) test during pre- and post-tests. They were then randomly assigned to either PLYO or ISO group and completed 12 sessions of intervention over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The positive effects of IST on CMJ performance have been evident in several studies (4,25,26). However, only one group of researchers has reported the effects of IST on CMJ forcetime data (26).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The positive effects of IST on CMJ performance have been evident in several studies (4,25,26). However, only one group of researchers has reported the effects of IST on CMJ forcetime data (26).…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of IST on CMJ performance have been evident in several studies (4,25,26). However, only one group of researchers has reported the effects of IST on CMJ forcetime data (26). It was reported that significant increases in CMJ height and countermovement depth were observed after performing IMTP and isometric ankle plantar flexion for 12 training sessions over 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations